Incentive Spirometry dan Chest Therapy Efektif Dalam Mengurangi Kekambuhan Pada Kondisi Asma Bronkial - Nova Relida Samosir; Diki Ananda (LPPM Universitas Abdurrab, 2020)
Background: Asthma bronchiale is a chronic respiratory disease that be marked inflammation chronic respiratory that involve kind of inflammation cell and mediators that interact wich each other so that produce physiogical changes and respiratory structure. Prevalence asthma case in Indonesia based on research result basic health (RISKESDAS) on 2013 to show that age 25-34 years have prevalence asthma the highest 5,7% and age under 1year prevalence asthma lowest of 1,5%. This research purposes to know the effectiveness gived Incentive spirometry and chest therapy to reduced symptoms recurrence that be measured by asthma control test and incentive spirometry. Research methods in case study that served in the form descriptive narrative. This research subject consist of one asthma bronchial sample with persistent degree moderate that fulfill criteria sample/ research. This is done 16 times therapy begins at date 04 february 2020 until 02 april 2020 in labotary manual therapy 1 D-III physiotherapy of Abdurrab University. Result: Evaluation with use asthma control test is obtained results is descreased symptoms recurrence and ecnhanment asthma control test from score 16 (Uncontrolled asthma) to be score 22 (Partially controlled asthma). Conclusion of the case study modality Incentive spirometry and chest therapy the results isthat decreased symptoms recurrence and increased of value force vital capacity (FVC) and force expired volume in one second (FEVÂ¹) on lung function Keywords : Asthma bronchiale, Incentive Spirometry, Chest Therapy, Postural Drainage, Tapotement, Asthma Control Test (ACT)